A Critical Look at Oppositional Culture and the Race Gap in Education. (12th May 2013) - Mangino, William
Abstract : This paper offers a sociological critique of the perceived Black-White gap in education and of the theory of "opposition" that underpins it. The literature extending back a century discusses how oppressed and segregated groups adopt attitudes opposed to those who oppress and contain them. Failure to situate the current oppositional culture in this larger body of literature makes opposition seem specific to Black Americans; it is not. Further, among people with similar economic resources, Black Americans have higher educational aspirations and go to college more than comparable Whites. The continued framing of a "race gap" without reference to economic circumstances reifies race and lays the blame for educational failure on schools, teachers, families, and students, when the real culprits are social and economic issues like jobs, wages, and residential segregation. But because politically we are unwilling to deal with these larger socioeconomic issues, educational professionals are compelled to practice as if economic inequality and poverty do not matter, but in fact they do. Because Black Americans are disproportionately represented in lower economic strata, a spurious correlation exists in professional and popular discourse that mistakenly identifies Black people as "opposed" to education. Net of socioeconomic status, Black Americans are no more opposed than anyone else.